Diagnostic Tools for Onchocerciasis Elimination Programs. Issue 11 (November 2015) - Vlaminck, Johnny; Fischer, Peter U.; Weil, Gary J.
Abstract : Onchocerciasis (river blindness) is a major public health problem in sub-Saharan Africa. Major disease-control programs have greatly reduced both disease and infection prevalence by mass distribution of donated ivermectin. Recent studies have shown that local elimination was achieved in some areas following many years of ivermectin. The global health community has recently decided to build on these successes with a new program that aims to eliminate onchocerciasis. Diagnostic tests that were useful for identifying priority areas for disease prevention may not be adequate tools for elimination programs. This paper reviews available and emerging diagnostic tests for onchocerciasis and considers how they might be best employed during different stages of onchocerciasis elimination programs. Trends: New diagnostic approaches are needed for onchocerciasis elimination programs. This paper reviews available and emerging diagnostic tests for onchocerciasis. Different tests may be required for different stages of elimination programs. Additional research is needed for mapping hypoendemic areas and on establishing endpoints.